Grounding Ocean Ethics While Sharing Knowledge and Promoting Environmental Responsibility: Empowering Young Ambassadors as Agents of Change - Cappelletto, Margherita; Giuffredi, Rita; Kastanidi, Erasmia; Vassilopoulou, Vassiliki; L'Astorina, Alba (Frontiers in Marine Science, 2021)
Actions addressing youths and marine science for ‘ambassadorship’ are increasingly being implemented via dedicated programmes at European and global level within relevant policy frameworks, as a way for fostering the exchange of knowledge and cross-fertilizing practices among countries and basins. These programmes are conceived to address the future generations of scientists, entrepreneurs, policy makers and citizens, to promote awareness and shared responsibility on the sustainable use of marine resources in an authentic and credible way, through the empowerment of young researchers and professionals, communicators or activists. Thus, such ambassadors are well positioned to act as agents of change, improving the dimension of Ocean Ethics related to inclusive governance, especially necessary for an equal, just and sustainable management of multi-actor and transboundary socio-environmental contexts. Pivoting on the Young Ambassadors’ Programme developed in the framework of the BlueMed Research and Innovation (R&I) Initiative for Blue Jobs and Growth in the Mediterranean area as case-practice, the article proposes some reflections about the long-term perspective of such experiences, outlining an emerging physiognomy of the “One Ocean Ambassadors”, as well as discusses their potential to build the next generation of responsible scientists, citizens and decision makers and to further embed ethics principles in research-based marine governance. In addition, it addresses process-related elements, including balancing advocacy and ethics and reflecting on the role of science communication. To further consolidate this practice, it finally seeks to incorporate the intercultural aspects to connect the local to the global dimension towards an ocean governance which is sustainable and value-based.